Assessing the Factors Influencing the Choice between Dividends and Share Repurchases - Abdul Rahman; Ratna Sari (Amkop Management Accounting Review (AMAR), 2024)
This study aims to examine the factors influencing the choice between dividends and share repurchases in corporate finance. Using a comprehensive literature review, this research explores the financial, strategic, and governance considerations that shape payout decisions within firms. The research design synthesizes insights from theoretical frameworks and empirical studies to provide a nuanced understanding of the complexities underlying dividend and share repurchase policies. Findings indicate that profitability, market timing, financial constraints, and managerial incentives are critical determinants of payout decisions, reflecting the dynamic nature of capital allocation processes. The discussion emphasizes the importance of aligning managerial interests with shareholder objectives through effective corporate governance mechanisms and transparent disclosure practices. The study's implications underscore the need for corporate finance practitioners and policymakers to adopt a multidimensional approach to payout decisions, integrating financial, strategic, and market perspectives to optimize shareholder value and mitigate risks associated with capital allocation strategies. By addressing these research gaps, scholars can contribute to a deeper understanding of the factors influencing payout decisions and inform evidence-based strategies for sustainable value creation in the corporate sector.